2017
DOI: 10.1111/bph.13844
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyeicosapentaenoic acids and epoxyeicosatetraenoic acids attenuate early occurrence of nonalcoholic fatty liver disease

Abstract: The ω-3 polyunsaturated fatty acids (PUFAs) mediate protective effects on several metabolic disorders. However, the functions of their metabolites in the early stage of nonalcoholic fatty liver disease (NAFLD) are largely unknown. EXPERIMENTAL APPROACHMice were fed a control diet, high-fat diet (HFD) or ω-3 PUFA-enriched HFD (ω3HFD) for 4 days and phenotypes were analysed. LC-MS/MS was used to determine the eicosanoid profiles. Primary hepatocytes and peritoneal macrophages were used for the mechanism study. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…5-HEPE (LOX product), which was increased in the USF+EtOH group vs . USF alone, is known to reduce the inflammatory response of macrophages [ 72 ]. The marked elevation of hepatic 18-HEPE (COX product) by EtOH in both SF and USF dietary groups is of particular interest because this EPA-derived metabolite is the precursor to the resolvins of the E-series (RvE), further suggesting that inflammation and resolution of inflammation in our experimental model of ALD are tightly connected processes.…”
Section: Discussionmentioning
confidence: 99%
“…5-HEPE (LOX product), which was increased in the USF+EtOH group vs . USF alone, is known to reduce the inflammatory response of macrophages [ 72 ]. The marked elevation of hepatic 18-HEPE (COX product) by EtOH in both SF and USF dietary groups is of particular interest because this EPA-derived metabolite is the precursor to the resolvins of the E-series (RvE), further suggesting that inflammation and resolution of inflammation in our experimental model of ALD are tightly connected processes.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of dietary fatty acids may have a role in the development of NAFLD, and conversely, may be an alternative source for decreasing deleterious NAFLD effects. Therefore, the composition of liver fatty acids may be involved in hepatic damage [ 122 , 123 ]. Dietary patterns are a combination of foods that are consumed by individuals and the amount of nutrients may produce synergistic health effects.…”
Section: Fatty Acids and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Therefore, the activation of pro-inflammatory cytokines, as well as the activation of the JNK pathway by palmitate in macrophages, decreased with a mixture of 17,18-EEQ, 5-HEPE, and 9-HEPE, which are identified as the efficient components of these metabolites, including HEPEs and EEQs. Herein, the results have demonstrated that the mixture (17,18-EEQ, 5-HEPE, and 9-HEPE) may be an alternative therapy to prevent the early stages of NAFLD by inhibiting adipose tissue macrophage infiltration and systemic inflammation via cJun-N-terminal-kinase (JNK) signaling [ 123 ].…”
Section: Fatty Acids and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…The beneficial effects of n- 3 PUFA on oxidative stress, inflammation, and TAG accumulation in the liver make them attractive candidates for NAFLD treatment. In another recent study, a targeted metabolomics approach was applied to determine the plasma and liver eicosanoid profiles in mice fed a control diet, high-fat diet (HFD) or n- 3 PUFA supplemented HFD (ω3-HFD) for 4 days [ 139 ]. The plasma concentrations of several hydroxyeicosapentaenoic acids (HEPEs) and epoxyeicosatetraenoic acids (EEQs) were reduced by a short-term HFD and were markedly increased by the ω3-HFD, suggesting a critical role of these metabolites in the protective effects of n- 3 PUFA on NAFLD.…”
Section: Application Of Omics Technologies In Liver Diseasesmentioning
confidence: 99%
“…Thus, a mixture of these three n- 3 PUFA metabolites was injected intraperitoneally into mice fed the control diet and HFD. The mixture significantly ameliorated short-term HFD-induced lipid accumulation in the liver and adipose tissue inflammation [ 139 ].…”
Section: Application Of Omics Technologies In Liver Diseasesmentioning
confidence: 99%